Https://invertebratefungi.org/: an expert-curated web-based platform for the identification and classification of invertebrate-associated fungi and fungus-like organisms. (1st April 2022) - Wei, De-Ping; Gentekaki, Eleni; Hyde, Kevin D; Xiao, Yuan-Pin; Luangharn, Thatsanee; Tian, Qing; Wang, Yuan-Bing; Lumyong, Saisamorn
Abstract: Fungi are the major decomposers in terrestrial and aquatic ecosystems, playing essential roles in biogeochemical cycles and food webs. The Fungi kingdom encompasses a diverse array of taxa that often form intimate relationships with other organisms, including plants, insects, algae, cyanobacteria and even other fungi. Fungal parasites of insects are known as entomopathogenic fungi and are the causative agents of serious disease and/or mortality of their hosts. Entomopathogens produce distinct metabolic compounds with roles in pathogenicity, virulence and host–parasite interactions. Thus, the potential of discovering new bioactive compounds useful in biocontrol and pharmaceutical industries is high. Given the significance of entomopathogenic fungi, the rapid research advances and the increased interest, it has become necessary to organize all available and incoming data. The website https://invertebratefungi.org/ has been developed to serve this purpose by gathering and updating entomopathogenic genera/species information. Notes of entomopathogenic genera will be provided with emphasis on their taxonomic status. Information on other invertebrates, such as rotifers, will also be included. Descriptions, photographic plates, information on distribution and host (where applicable) along with molecular data and other interesting details will also be provided. The website is easily and freely accessible to users. Instructions concerning the platform architecture and functionality of the website are introduced herein. The platform is currently being expanded and will be continuously updated as part of the effort to enrich knowledge on this group of fungi. Database URL : https://invertebratefungi.org/